Toxicity and antimicrobial potential of some Philippine sponges - Togle-Tayo, Gilma D.
Five species of marine Philippine sponges from Sebaste, Guimaras were each extracted with water and methanol. The extracts were tested for fish toxicant activity on fry of Oreochromis niloticus in a 96-hour bioassay. Testa for antimicrobial activity of the extracts were done on seven representative microorganisms. The aqueous and methanol extracts of Dysidea herbacea showed highly potent ichthyotoxicity and bactericidal activity. The methanol extract ofSpirastrella vagabunda and the aqueous extracts of Gelliodes callista, sigmadocia symbiotica, and callysponqia exigua were toxic to fish. The aqueous extract of S. vagabunda and the methanol extracts of G. callista, S. symbiotica and c. exigua were not toxic. Aside from both extracts of D. herbacea antimicrobial activity was observed in the methanol extracts of S. symbiotica and s. vagabunda which inhibited Bacillus subtilis S-25. All the other extracts did not show any activity against any of the test microorganisms.